Examining the Impact of Organizational Commitment and Work-Life Balance on Nurses' Job Performance at Regional General Hospital X in Jakarta: The Mediating Role of Job Satisfaction - Djajasasana, Caroline Novenia; Palupi Meilani, Yohana F. Cahya (Jurnal Economic Resource, 2025)
Hospitals require health workers with optimal performance to ensure high quality services, especially nurses who act as the frontline in patient care. Optimal nurse performance can improve patient safety, operational efficiency, and patient satisfaction. Maintaining this level of performance is a major challenge for hospital management. This study aims to analyse the effect of organisational commitment and work-life balance on nurses' job performance at Regional General Hospital X in Jakarta, with job satisfaction as a mediating variable. This study used a quantitative approach with a cross-sectional design, using a structured questionnaire distributed to non-civil servant nurses who have worked for at least one year at the hospital. The study involved a total of 100 respondents, consisting of 30 participants in the preliminary study and 70 in the main study. Data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that both organisational commitment and work-life balance have a significant positive influence on job performance, both directly and indirectly through the mediation of job satisfaction. This study provides managerial implications for hospital administrators to effectively maintain and improve nurses' performance.